European Border Conflicts: Failures and Inabilities of EU Foreign and Security Policy - Marsili, M. (Ciência 2019, 2019)
The EU represents one in a series of efforts to integrate Europe since World War II, and to achieve, inter alia, diplomatic stability and military security. Alongside non-international and international conflicts, a third category of armed conflict is emerging: hybrid, asymmetric, and transnational conflicts which involve state and non-state actors such as insurgents and terrorists. Unconventional conflicts are among the trend topics of defense and security, and they pose a threat to the stability of international order. Hybrid conflicts, involving state and non-state actors, characterize the post Cold War era. These conflicts challenge the ability of international organizations to address them, and so far the EU was unable to settle them. The EU is not able to achieve an ownership in the field of peace, stability and security at its borders, and and his claim to be a global actor proves weak-willed. It would be useful to investigate the reasons for this incapacity: lack of a real and exclusive autonomy in matters of foreign policy; lack of a European army; subjection to US-led NATO; national interest of EU member states.